Editorial Foreword - Jack Whitehead; Marie Huxtable (Educational Journal of Living Theories)
EJOLTs 2023, Volume 16 is the first volume to be comprised completely by content published as soon as the Editorial Board has accepted it for publication. The change from publishing just twice a year has been introduced for a number of reasons. EJOLTs has always been a web-based journal and practitioners have been encouraged to make the best use of innovations in technology in their research and to communicate their accounts of their Living Educational Theory Research. However, EJOLTs continued to follow many of the practices of traditional print-based journals, including publishing issues at predetermined moments in time. Developments in technology and recognition and appreciation of what constitutes educational knowledge by the global Academy now open new possibilities of publishing. Hence the decision to change to publishing, as papers are ready, rather than gathering contents for issues to publish twice a year